Home-based low-level light therapy using a commercial LED mask for dry eye disease - Luca Scuderi; Serena Fragiotta; Chiara Ciancimino; Gianluca Scuderi (International Ophthalmology, 2026)
Abstract Purpose Light-based therapies, including low-level light therapy (LLLT), have recently emerged as promising non-invasive approaches for dry eye disease (DED). This study evaluates the impact of a consumer-grade home-based LED Beauty Mask on DED parameters. Methods This retrospective observational cohort study included 20 postmenopausal women (20 eyes) diagnosed with moderate DED and MGD who underwent cosmetic treatment using the LED Beauty Mask Koled®. The device was used for 20-min sessions on alternate days over a 3-week period. Clinical evaluations were performed at baseline, 3 weeks (T1), and 2 weeks (T2) after the last treatment and included tear osmolarity, tear film break-up time (TBUT), Schirmer I test, corneal fluorescein staining, and the Ocular Surface Disease Index (OSDI). Results Tear osmolarity demonstrated a significant improvement over time ( P < 0.001), with the most pronounced change observed at T1. Tear film stability, assessed by TBUT, also improved significantly ( P = 0.001). Subjective symptoms measured by OSDI showed a significant and sustained reduction ( P < 0.001). No significant changes were observed in Schirmer I test values ( P = 0.29). Corneal fluorescein staining present at baseline resolved by the final follow-up. Four eyes (20%) exhibited osmolarity values below the measurable range after treatment. No discomfort or adverse events were reported. Conclusions This study suggests that a cosmetic LED mask may provide symptomatic and functional improvement in DED when repurposed for ocular use. Although preliminary and limited by sample size, these findings support further investigation through controlled clinical trials.